Evaluasi Usability Sistem Pembelajaran Online dan Interaktif (SIMPONI) di STMIK MDP menggunakan Use Questionnaire - Meilyana Winda Perdana (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
SIMPONI implementation in the learning system can help the teaching and learning process at STMIK MDP. Measurements using Usability emphasize aspects of effectiveness, efficiency and user satisfaction. This study aims to determine the level of SIMPONI usability and evaluate the use of SIMPONI as a support in the learning process in Higher Education. The instrument used in this measurement is to use the USE Questionnaire containing usefulness (U), Ease of use (EOU), Ease of Learning (EOL) and Satisfaction (S) variables. Each of these variables will be broken down into a package of statements in a questionnaire that uses a Likert scale. The test was carried out using statistical calculations with SPPS application tools and number processing applications (excel). Data in this study were collected using a questionnaire distributed to 259 respondents consisting of students and lecturers. The results of this study are the SIMPONI usability level and the SIMPONI evaluation, overall the SIMPONI usability level is 83.5% and is included in the